Phytochemical and Bioactivity Evaluation of Bee Pollen and Androecia of Castanea, Salix, and Quercus Species - Nisa Beril Sen; Irena Vovk; Hasan Kırmızıbekmez; Etil Guzelmeric (Antioxidants)
Qualitative and quantitative differences in the chemical composition between bee pollen originated from Castanea sativa (Türkiye and Slovenia), Salix spp. (Türkiye and Slovenia), and Quercus spp. (Türkiye) and androecia of Castanea sativa, Salix alba, and Quercus pubescens (apetalous trees) were evaluated for the first time by new high-performance thin-layer chromatography (HPTLC) and ultra-performance liquid chromatography (UPLC) methods using marker compounds. N1,N5,N10-tricaffeoylspermidine was isolated, and its structure was elucidated by nuclear magnetic resonance (NMR) and high-resolution mass spectrometry (HRMS). It was the main and the marker compound common to bee pollen (≈3–41 mg/g) and androecia (≈3–6 mg/g) samples. To the best of our knowledge, this is the first report of the identification of N1,N5,N10-tricaffeoylspermidine in bee pollen originated from Salix spp. and androecia of C. sativa, S. alba, and Q. pubescens. The botanical origins of bee pollen were determined via phytochemical profiling using HPTLC-image analyses showing that bee pollen from the same botanical source had almost identical profiles regardless of collection location, geographical differences, and the bee race. In vitro tests and HPTLC-effect-directed analyses (EDAs) were performed to assess antioxidant and xanthine oxidase (XO) inhibitory activities of bee pollen, androecia, and N1,N5,N10-tricaffeoylspermidine. HPTLC-EDA combined with image analyses was used for comparing the activities of bee pollen, androecia, N1,N5,N10-tricaffeoylspermidine, and also other marker compounds (quercetin, myricitrin, hyperoside, quercitrin, isoquercitrin, and rutin). The remarkable bioactivity of N1,N5,N10-tricaffeoylspermidine was for the first time evaluated by HPTLC-EDA and in vitro tests. This is the first study performing HPTLC-XO inhibitory activity analyses on the HPTLC NH2 F254S plates. Further bioactivity studies on botanically and chemically well-characterized bee pollen samples are needed to aid in the use of bee pollen-containing supplements in the prevention and treatment of diseases.